PENDIDIKAN ADAB SEBAGAI ALTERNATIF PEMBELAJARAN DI MASA PANDEMI COVID 19 - khilmi Dzulqornain (Balitbangda Provinsi Lampung, 2020)
A person's personality is reflected in noble morals, he will deliver someone to high dignity. Lately noble manners are expensive and hard to find. The lack of understanding of the values ​​of etiquette contained in the Qur'an and the hadith will further aggravate the condition of one's personality. To form a noble person, the planting of manners towards children should be encouraged early on, because the formation will be easier than after the child has reached adulthood. With the outbreak of the covid-19 pandemic, which has a very significant impact on the education, it should be a momentum to review the demands of the education curriculum so far. Especially with no demands on completeness of curriculum targets and other academic parameters. The result show that the concept of etiquette in learning initiated by Aljarnuzi has a concept of courtesy learning which is classified into adab learning of students towards God, etiquette of student learning towards themselves, etiquette of student learning towards others (parents, teachers, and friends), and manners of learning students towards science. The recommendations in this study, all parties involved in education, especially for a student, should always apply the learning standards that have been initiated by Al-Jarnuji, in order to obtain success in learning, so as to obtain useful knowledge.